Characters of a new species of the Cretaceous genus †Loeblitoides affirm affinities to the extant ‘Syndicus group’ of Stenichnini (Coleoptera: Staphylinidae: Scydmaeninae) - Jałoszyński, Paweł; Szawaryn, Karol (Zootaxa, 2024)
A new species of Cenomanian Stenichnini is described, based on an inclusion in Myanmar amber: †Loeblitoides latus sp. nov. As a close relationship between †Loeblitoides and the extant genera Syndicus Motschulsky, Loeblites Franz, and Horaeomorphus Schaufuss was postulated, we used 3D visualization techniques based on micro-computed tomography to search for otherwise impossible to observe morphological details and find arguments supporting this hypothesis. A novel structure, a pair of basal elytral foveae connected in a peculiar way, found in †L. latus, indeed supports the previous views, as it is unique for the extant ‘Syndicus group’. The diagnosis of †Loeblitoides is emended to include new findings.